Simulasi Cfd Ang Storage Dengan Metana Sebagai Adsorbat Dan Karbon Aktif Sebagai Adsorbennya (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Increased air pollution and fuel price volatility to the attention of the world that began to study alternative energy sources. Natural gas is an alternative that can replace fuel, natural gas used was methane. There are 3 natural gas  storage process LNG, CNG and ANG. LNG  requires extremely low temperatures  to  liquefy  the methane  gas whereas CNG  requires  a very  high pressure of 200 bar for storing methane, both of these processes require a very expensive cost, whereas ANG only requires a pressure of 4 bar for storing methane so that ANG is an excellent alternative possible. ANG process has been studied experimentally, while the simulation is still very  rare. This study uses  the simulation computational fluid dynamics (CFD) for  the ANG. This  modeling  using Fluent.  From this  simulation  can be obtained  the distribution of temperature, pressure, adsorption capacity and adsorption rate of capacity during the adsorption process occurs. The study was conducted at a pressure of 30 bar and a temperature of 300 K, in order to obtain the result of pressure and temperature distribution are influenced by the UDF equation  source  terms and methane gas adsorption capacity at the  time of 54000  seconds  is 0.069797 kg/kg, and the rate of adsorption at the time of 54000 seconds is 5.1x10-9kg/kg.s. Keywords: Simulasi, CFD, Fluent, Adsorpsi, ANG, Karbon aktif